LANDMARK WATER WHISPER DI WADUK RIA RIO, PULOMAS DEMI MEREGENERASI KUALITAS AIR - Hellery, Patricia; Sutanto, Agustinus (Jurusan Arsitektur dan Perencanaan, 2025)
The phenomenon of quality degradation in the Ria Rio Reservoir, Pulomas is an example of negligence arising from the decline in water quality and activities that are continuously ignored. The decline and passivity are the main issues faced. This requires innovative solutions to restore the water ecosystem and raise awareness of the importance of water quality. With the approach of “behavioral architecture”, this study explores the potential integration of